Immigration: High Skilled vs. Low Skilled Labor? - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2011)
This policy analysis paper explores the implications for the host country population of alternative immigration policies. The two immigration options considered are a policy based on admitting primarily high-skilled workers and another that has the effect of admitting primarily low-skilled workers. The implications for the native-born population for their aggregate level of income, the distribution of their income by skill level, and the size of the income redistribution system are considered. The paper was prepared for the Productivity Commission of Australia.
Keywords: F22; J24; 330; immigrant impact; immigrant skills; immigration policy; Migrationspolitik; Qualifikation; Wirkungsanalyse; Bevölkerung; Einkommen; Australien